Analisa Dan Pemodelan E-Marketing Pada PT. Sinar Galesong Mandiri - Elisabeth; Alfin Chandra (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2021)
The goal of this research is to increase the market for Suzuki Automatic motorbike product in Makassar city so that can help company in selling the Automatic motorbike product and also can compete with other companies. PT. Sinar Galesong Mandiri is using social media as a marketing method to reach millennial age consumer. The marketing systems through social media is the most marketing methods widely used today keeping up with the rapid use development of information technology. E-marketing strategy using social media plays an important role in the marketing, sales and customer service processes. The outcome of this research is an analysis and modelling of a marketing system that can assist marketing in planning the marketing for Suzuki Automatic motorbike product targeting the millennial consumers.